Nitrate and nitrite residues in Greek pastirma - TYRPENOU, A. E.; GOUTA (E.H. ΓΟΥΤΑ), E. H.; TSIGOURI (Α.Δ. ΤΣΙΓΟΥΡΗ), A. D.; VLASIOTIS (Χ.Ν. ΒΛΑΣΙΩΤΗΣ), Ch. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this research, for the investigation of the nitrate and nitrite content of Greek pastirma samples coming from several Greek meat processing factories were examined. Nitrate and nitrite determination was carried out following the standard methods of the International Standard Organization ISO No. 2918/751 and 3091/75.2 According to these Standard Operating Procedures-SOPs, reducing capacity of cadmium column should always has to be >90%. Because this critical point usually causes problems [never was >70%], we succeeded and validated this point by amending 3 points of the Standard Operating Procedure [SOP]. These amendments referred to the replacement of the buffer pH 9,6 of the cadmium column with the buffer pH 12,0 according to the method of Margeson et al., 1980.3 The result was that the reducing capacity of the cadmium column increased from 70% to 90-105%. Thirty pastirma samples have been tasted and the concentrations determined ranged from 0,85 to 189,65mg/kg for nitrites and from 2,66 to 639,67mg /kg for nitrates expressed as sodium nitrite. Nitrites, in 56,66% of the samples and nitrates in 83,33% of the samples were ranging in the limits foreseen by the Greek Legislation.